The relationship between curvature, flexibility and persistence length in the tropomyosin coiled-coil - Li, Xiaochuan (Edward); Lehman, William; Fischer, Stefan (Journal of structural biology, 2010)
The inherent flexibility of rod-like tropomyosin coiled-coils is a significant factor that constrains tropomyosin’s complex positional dynamics on actin filaments. Flexibility of elongated straight molecules typically is assessed by persistence length, a measure of lengthwise thermal bending fluctuations. However, if a molecule’s equilibrium conformation is curved, this formulation yields an “apparent” persistence length (∼100nm for tropomyosin), measuring deviations from idealized straight conformations which then overestimate actual dynamic flexibility. To obtain the “dynamic” persistence length, a true measurement of flexural stiffness, the average curvature of the molecule must be taken into account. Different methods used in our studies for measuring the dynamic persistence length directly from Molecular Dynamics (MD) simulations of tropomyosin are described here in detail. The dynamic persistence length found, 460±40nm, is ∼12-times longer than tropomyosin and 5-times the apparent persistence length, showing that tropomyosin is considerably stiffer than previously thought. The longitudinal twisting behavior of tropomyosin during MD shows that the amplitude of end-to-end twisting fluctuation is ∼30° when tropomyosin adopts its near-average conformation. The measured bending and twisting flexibilities are used to evaluate different models of tropomyosin motion on F-actin.